Identification of potentially toxic Pseudo‐nitzschia (Bacillariophyceae) in New Zealand coastal waters, using lectins - Lesley L. Rhodes (New Zealand Journal of Marine and Freshwater Research, 1998)
Identification of species within the do‐moic acid‐producing diatom genus Pseudo‐nitzschia is vital for biotoxin monitoring and decisions regarding shellfish harvesting, particularly when blooms are occurring. Several Pseudo‐nitzschia species produce high concentrations of domoic acid per cell, whereas others are non‐toxic, but all have similar morphologies using standard brightfield light microscopy. FITC‐conjugated lectins discriminated between the New Zealand derived species tested in this study, except for P. delicatissima and P. pseudo‐delicatissima . These results differ from those reported for Pseudo‐nitzschia species isolated from Galician (Spanish) waters, which suggests variability in production of surface sugars by these diatoms depending on geographical origin and/or environmental conditions. Ribosomal RNA‐targeted oligo‐nucleotide probes, at present being field trialled in several countries including New Zealand and the United States, are therefore still the preferred method of Pseudo‐nitzschia species identification underpinning New Zealand's biotoxin risk assessment programmes.